Ultra-low temperature toughened nylon glass fiber reinforced composite material and preparation method and application thereof

By using the synergistic effect of short carbon chains and long carbon chain nylon composites, glass fiber reinforced and specific toughening agents and crosslinking agents in nylon materials, ultra-low-temperature toughening nylon glass fiber reinforced composite materials have been developed, solving the problem of brittle cracking of traditional nylon materials at ultra-low temperatures, and improving high strength, toughness and impact resistance. They are suitable for engineering applications under extreme cold conditions.

CN119735950APending Publication Date: 2025-04-01NINGBO JINGCI TECH DEV CO LTD

Patent Information

Application Number
CN202411928367.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional nylon materials have significantly reduced toughness and impact strength in ultra-low temperature environments, resulting in brittle cracks, limiting their application in extreme climatic conditions.

Method used

Ultra-low-temperature toughened nylon glass fiber reinforced composite material is used to form a high-performance composite material through the combination of short carbon chain nylon and long carbon chain nylon, glass fiber reinforcement, maleic anhydride modified elastomer toughening, aminocage-type silsesquioxane cross-linking and additives.

Benefits of technology

At -50℃, the composite material maintains high strength and high toughness. The impact strength of the simple-supported beam notched is ≥15kJ/m2. The impact rod impact test will not break at least once, meeting the engineering application needs under extremely cold conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735950A_ABST
    Figure CN119735950A_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-low temperature toughened nylon glass fiber reinforced composite material, a preparation method and an application thereof. The composite material comprises 50-70 parts of nylon resin, 20-40 parts of glass fiber, 5-10 parts of toughening agent, 0.1-5 parts of cross-linking agent and 0.1-10 parts of other auxiliary agents by weight; the toughening agent comprises a maleic anhydride modified elastomer; the cross-linking agent comprises an amino cage silsesquioxane; the composite material has a simple supported beam notched impact strength of ≥15 kJ / m at -50 °C 2 The impact rod is tested at 50°C without breaking at least once. The ultra-low temperature toughened nylon glass fiber reinforced composite material of the present invention has both high impact strength and mechanical toughness in a wide temperature range, especially in an ultra-low temperature environment, and can meet the needs of railways, highways, electricity and other facilities in cold areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to an ultra-low temperature toughened nylon glass fiber reinforced composite material and a preparation method and application thereof. Background Art

[0002] As an engineering plastic with excellent performance, nylon (polyamide) material is widely used in machinery, automobiles, electronics and electrical, rail transit and other fields due to its high strength, wear resistance, chemical corrosion resistance and good processing performance. In the railway system, nylon material is used to manufacture track fasteners, cable protection sleeves, carriage interior parts, etc. due to its good toughness and electrical insulation properties. However, in ultra-low temperature environments, as the temperature decreases, the toughness and impact strength of traditional nylon materials will decrease significantly, and brittle cracks will easily occur, limiting its application in extreme climatic conditions. Therefore, in order to meet the use needs of railway facilities in cold areas (especially extremely cold areas where the temperature drops to -50°C), the development of toughened nylon materials with excellent low-temperature resistance has become a research focus.

[0003] Invention CN110437611B discloses a reinforced and toughened ultra-low temperature resistant nylon composite material, comprising: 55-75 parts of nylon resin, 15-30 parts of glass fiber, 5-12 parts of toughening agent, and 0.5-2 parts of lubricant; the toughening agent is a mixture of amino-terminated polydimethylsiloxane, epoxy-terminated polydimethylsiloxane and silicone elastomer toughening agent; the glass fiber is a glass fiber modified by an amino- or epoxy-containing silane coupling agent. The reinforced and toughened ultra-low temperature resistant nylon composite material of the invention can be used in the preparation of high-speed railway accessories in extremely cold climate areas and in the fields of electronics, communications, and aerospace in ultra-low temperature environments. The invention specifically adopts a combination of nylon 6 and nylon 66, and combines a toughening system to obtain an ultra-low temperature resistant nylon composite material. The main contribution of the invention lies in the configuration of the toughening system, and the low-temperature mechanical properties are still insufficient, the toughening efficiency and effect are limited, and the manufacturing cost is relatively high.

[0004] Invention CN115746557 B discloses a toughened long carbon chain nylon and its preparation method and application, which includes the following components by weight: 100 parts of long carbon chain nylon resin, 1-20 parts of plasticizer, 1-25 parts of toughening agent and 0.05-0.5 parts of antioxidant, wherein nylon 1018 toughening agent is made from octadecanoic acid, decanediamine and trifunctional polyetheramine as raw materials. However, this invention mainly focuses on the room temperature and low temperature flexibility of long carbon chain nylon, which can meet the requirements of nylon hoses for automobile pipeline systems and is used in automobile pipeline systems. However, due to the limitations of the characteristics of long carbon chain nylon, the low temperature mechanical strength of the composite material is limited, and it cannot meet the requirements of material performance in ultra-low temperature and high stress environments.

[0005] Therefore, how to develop a nylon composite material that has both high impact strength and mechanical toughness in an ultra-low temperature environment, especially to meet the actual needs of high-stress facilities such as railways in cold regions, is an important technical problem that technical personnel in this field need to solve urgently. Summary of the invention

[0006] In view of the defects existing in the above-mentioned prior art, the present invention provides an ultra-low temperature toughened nylon glass fiber reinforced composite material and a preparation method and application thereof, which can meet the actual needs of high-stress facilities such as railways in cold regions.

[0007] In a first aspect, the present invention provides an ultra-low temperature toughened nylon glass fiber reinforced composite material, which comprises, by weight:

[0008]

[0009] The toughening agent includes a maleic anhydride modified elastomer;

[0010] The crosslinking agent includes amino cage silsesquioxane;

[0011] The composite material has a simple supported beam notched impact strength of ≥15 kJ / m2 at -50°C, and an impact rod does not break after at least one -50°C impact test.

[0012] The composite material of the present invention is based on nylon resin as the matrix and glass fiber as the reinforcing material, combined with toughening agent, cross-linking agent and auxiliary agent and other components, giving full play to their respective advantages. Nylon resin has excellent mechanical strength, heat resistance and wear resistance, and the addition of glass fiber significantly improves the strength, rigidity and dimensional stability of the material, so that the composite material exhibits excellent mechanical properties at room temperature. However, nylon resin itself is relatively brittle in low temperature environment, and the reinforcing effect of glass fiber may also lead to a decrease in toughness. These factors make it difficult for traditional nylon glass fiber reinforced composite materials to meet the needs of engineering applications under ultra-low temperature conditions (such as -50°C).

[0013] To overcome the above problems, the present invention improves the low-temperature toughness of the material with a flexible molecular chain by introducing a toughening agent (such as maleic anhydride grafted ethylene-octene copolymer and ethylene propylene diene monomer rubber); at the same time, a cross-linked network is formed in the molecular structure by an amino cage silsesquioxane crosslinker to enhance the overall strength and low-temperature stability of the material; with additives such as antioxidants, lubricants and dispersants, the processing performance and long-term use performance of the material are improved. The synergistic effect of each component significantly enhances the impact resistance and mechanical properties of the composite material in an ultra-low temperature environment, so that it still has high strength and high toughness at -50°C, meeting the engineering requirements under extremely cold conditions. And the room temperature mechanics and mechanical properties of the composite material are also very excellent, the room temperature simply supported beam notched impact strength ≥30kJ / m2, bending strength ≥200MPa, tensile strength ≥130MPa, elongation at break ≥4%, and the impact rod impact test is at least 6 times without breaking, so that the composite material has a wide range of use temperature, which can meet the use requirements of railways, highways, electricity and other facilities in most areas.

[0014] Preferably, the other additives include at least one of an antioxidant and a lubricant;

[0015] The antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant;

[0016] The lubricant includes at least one of silicone powder and ethylene bisstearamide.

[0017] Preferably, the glass fiber has a length of 3-6 mm and a diameter of 10-20 μm, preferably 13-17 μm, and the glass fiber is surface treated with a silane coupling agent.

[0018] The present invention preferably uses chopped glass fibers, and the length of the glass fibers is controlled within a specific range (such as 3-6 mm), which can form a uniform distribution in the matrix and give full play to the reinforcing effect. As a reinforcing phase, it combines with the matrix material to form a composite structure, significantly improving the mechanical strength, dimensional stability and heat resistance of the material. At the same time, the silane coupling agent reacts with the molecular chain in the glass fiber and the nylon resin through its active functional group to form a chemical bond or hydrogen bond on the interface, improve the interface compatibility and bonding strength of the two, reduce stress concentration, and thus improve the comprehensive mechanical properties of the composite material.

[0019] The present invention adopts chopped glass fibers treated with silane coupling agents, which can form a strong interface bond with the nylon resin matrix, effectively improving the strength and rigidity of the composite material. At the same time, the appropriate fiber length ensures the reinforcement effect while avoiding uneven dispersion of excessively long fibers during processing or affecting the toughness of the material. Combined with the toughening agent and cross-linking agent system of the present invention, the strength and toughness of the material are further balanced, so that the composite material exhibits excellent impact resistance and stability in a low temperature environment, meeting the engineering application requirements under extremely cold conditions. The silane coupling agent can use the silane coupling agent commonly used in the art, such as γ-aminopropyltriethoxysilane (silane coupling agent KH550), (3-glycidoxy)propyltrimethoxysilane (silane coupling agent KH560), etc., and the ratio of the amount of silane coupling agent to the mass of glass fiber is about 1: (5-50).

[0020] Furthermore, the glass fiber is surface treated with a silane coupling agent, specifically comprising the following steps:

[0021] (1) mixing a mercaptosilane coupling agent and glass fiber to form a hydrophobic glass fiber;

[0022] (2) The hydrophobic glass fiber is treated with an oxidant to oxidize the thiol groups of the hydrophobic glass fiber to form disulfide bonds, thereby obtaining modified glass fibers.

[0023] Wherein, the oxidant can be selected from oxidants commonly used in the art, including at least one of hydrogen peroxide, organic peroxide, hypochlorite, perborate, permanganate, bromine, and nitric oxide. The mercaptosilane coupling agent can be selected from 3-mercaptopropyltrimethoxysilane or 3-mercaptopropylmethyldimethoxysilane. The amount of the oxidant is preferably sufficient to oxidize at least most of the mercaptan groups of the mercaptosilane coupling agent, for example, an excessive amount of the oxidant can be used to convert all mercaptan groups into disulfides. The modified glass fiber with disulfide bonds on the surface is particularly suitable for matching with the modified elastomer in the toughening agent, while the glass fiber improves the mechanical strength of the composite material, weakening its negative effect on low-temperature toughness.

[0024] Preferably, the nylon resin comprises a compound of short carbon chain nylon and long carbon chain nylon;

[0025] The short carbon chain nylon includes at least one of nylon 6 and nylon 66;

[0026] The long carbon chain nylon includes at least one of nylon 12, nylon 612, nylon 1010 and nylon 1012.

[0027] Preferably, the short carbon chain nylon is premixed with a toughening agent;

[0028] The long carbon chain nylon is pre-crosslinked with at least a portion of the crosslinking agent;

[0029] The mass ratio of short carbon chain nylon to long carbon chain nylon is (1-6):(1-3).

[0030] The short carbon chain nylon (such as nylon 6 and nylon 66, etc.) used in the present invention has high crystallinity and rigidity, giving the composite material excellent mechanical strength and wear resistance, but due to the short molecular chain, toughness and low temperature performance are relatively weak. Long carbon chain nylon (such as nylon 12, nylon 612, nylon 1010 and nylon 1012, etc.) exhibits excellent toughness, cold resistance and dimensional stability because of its good molecular chain flexibility and low crystallinity. Compared with the prior art, which only relies on toughening agents, reinforcing agents, cross-linking agents, etc. to improve the mechanical properties of composite materials, the present invention can achieve the complementarity of the performance of the two by compounding short carbon chain nylon with long carbon chain nylon in a specific mass ratio, and the main resin component of the composite material is more optimized from the matrix angle.

[0031] The pre-crosslinking of long carbon chain nylon and amino POSS crosslinker forms a partial crosslinking network through chemical reaction (Step 1). The principle is that the amino functional groups in the amino POSS molecules can react with the amide groups on the long carbon chain nylon molecular chain to generate stable chemical bonds, which is particularly helpful to fully combine the flexible long carbon chain nylon with the crosslinker, ensuring the structural stability and mechanical properties of the composite material. On the one hand, the crosslinking network improves the creep resistance of the material, making the composite material less likely to deform under high stress conditions; on the other hand, this crosslinking network provides additional molecular chain constraints in low temperature environments, reducing the risk of embrittlement of the material, thereby significantly improving the toughness and low temperature impact strength of the composite material. At the same time, the cage structure of POSS also gives the material higher dimensional stability and aging resistance. Later, in the blending melt treatment, the remaining amino functional groups on the amino POSS crosslinker can further react with the short carbon chain nylon to form a denser crosslinking network (Step 2), forming an overall network structure of the long carbon chain nylon and the short carbon chain nylon. Macroscopically, the composite material exhibits excellent mechanical strength and toughness at room temperature and ultra-low temperature. Taking long carbon chain nylon 1010 and short carbon chain nylon 66 as examples, the above two-step cross-linking reaction can be referred to the following reaction formula. The long carbon chain nylon and short carbon chain nylon of the present invention have multiple options, and the following examples are not limitations of the present invention.

[0032]

[0033] The surface activity of glass fiber is significantly improved after being treated with silane coupling agent, and it can be combined with nylon molecular chain to form strong interface bonding. In particular, the present invention adopts maleic anhydride grafted modified elastomer as toughening agent, and the modified glass fiber with disulfide bond on the surface is matched. After uniform mixing, the toughening agent and the disulfide bond on the surface of the glass fiber are matched to form a flexible coating layer, and this toughened flexible coating layer not only reduces the surface energy of the glass fiber, but also can effectively alleviate the problem of interfacial stress concentration between the fiber and the nylon matrix, and improves the toughness and impact strength of the composite material. When external force acts, the flexible characteristics of the toughening agent cause it to deform greatly, absorb energy and alleviate the generation and expansion of cracks, thereby improving the impact strength and fracture toughness of the material, and particularly showing excellent impact resistance under low temperature environment. The maleic anhydride grafted group has good polarity, can react with the amide group of the nylon matrix, form chemical bonds or physical interactions, significantly improve the interfacial compatibility between the glass fiber and the nylon matrix, improve the bonding force between the glass fiber and the matrix, and enhance the structural stability and mechanical properties of the composite material.

[0034] Preferably, the aminated cage silsesquioxane includes at least one of octaphenylamino cage silsesquioxane, octamethylamino cage silsesquioxane and octaethylamino cage silsesquioxane; more preferably, it is octaphenylamino cage silsesquioxane.

[0035] The maleic anhydride modified elastomer includes at least one of maleic anhydride grafted ethylene-octene copolymer and maleic anhydride grafted ethylene propylene diene monomer rubber.

[0036] In a second aspect, the present invention further provides a method for preparing the ultra-low temperature toughened nylon glass fiber reinforced composite material, comprising the following steps:

[0037] S1. Weigh nylon resin, glass fiber, toughening agent, cross-linking agent and other additives according to weight proportions;

[0038] S2, mixing nylon resin, toughening agent, cross-linking agent and other additives;

[0039] S3, adding glass fiber to the mixture, and melt-extruding and granulating to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material.

[0040] Preferably, the nylon resin includes a short carbon chain nylon resin and a long carbon chain nylon resin, and the glass fiber is surface treated with a silane coupling agent;

[0041] In step S1, the raw materials are configured into a first raw material group, a second raw material group, and a third raw material group, wherein:

[0042] The first raw material group includes short carbon chain nylon resin, toughening agent and other additives;

[0043] The second raw material group includes a long carbon chain nylon resin and a cross-linking agent;

[0044] The third raw material group includes glass fibers;

[0045] In step S2, the first raw material group is added from the main feed port of the extruder;

[0046] After the second raw material group is subjected to a pre-crosslinking treatment, it is added from the first side feeding port of the extruder;

[0047] In step S3, the third raw material group is added from the second side feeding port.

[0048] Preferably, in step S3, the operating temperature of the twin-screw extruder is set to 200-290° C., and the screw speed is set to 240-600 r / min.

[0049] More preferably, the temperature of the twin-screw extruder C1 feeding zone is 60-75°C, the temperature of the C2 heating zone is 265-280°C, the temperature of the C3 melting zone and the C4 homogenizing zone is 280-290°C, the temperature of the C5 mixing and plasticizing zone is 285-290°C (the temperature of some areas reaches 290°C, which is conducive to promoting micro-crosslinking reactions), the temperature of the C6 volatile removal zone is 265-275°C, the temperature of the C7 final melting adjustment zone is 260-275°C, the temperature of the C8 cooling zone is 260-270°C, the temperature of the C9 die head temperature control zone is 260-275°C, and the head temperature is 265-275°C.

[0050] In a third aspect, the present invention further provides a rail shock-absorbing pad, comprising the aforementioned ultra-low temperature toughened nylon glass fiber reinforced composite material or the ultra-low temperature toughened nylon glass fiber reinforced composite material obtained by the aforementioned preparation method provided by the present invention.

[0051] In a fourth aspect, the present invention also provides an application of the ultra-low temperature toughened nylon glass fiber reinforced composite material or the ultra-low temperature toughened nylon glass fiber reinforced composite material obtained by the aforementioned preparation method provided by the present invention in rail fastener systems, cable protection sleeves, car interior components, and rail shock-absorbing pads.

[0052] The present invention has at least the following beneficial effects:

[0053] (1) The present invention forms a high-performance ultra-low temperature toughened nylon glass fiber reinforced composite material by compounding short carbon chain nylon and long carbon chain nylon, reinforcing glass fiber, toughening with a toughening agent, crosslinking with an amino cage-type silsesquioxane, and synergistic action of an auxiliary agent.

[0054] (2) Short carbon chain nylon provides high strength and wear resistance, and long carbon chain nylon significantly improves toughness and cold resistance due to its molecular chain flexibility. The present invention achieves the complementary performance of the two by rationally compounding short carbon chain nylon and long carbon chain nylon. At the same time, the pre-crosslinking of long carbon chain nylon and amino POSS crosslinking agent forms a crosslinking network between molecules, improves the creep resistance and structural stability of the composite material, and reduces the risk of embrittlement of the material in a low temperature environment.

[0055] (3) Chopped glass fibers treated with silane coupling agents enhance the interfacial bonding between the fibers and the nylon matrix, improve the rigidity, strength and dimensional stability of the material, and avoid the problem of reduced toughness. In particular, modified glass fibers with disulfide bonds on the surface obtained by oxidation with mercaptosilane coupling agents can be combined with modified elastomers of toughening agents and then combined with the matrix through flexible molecular chains, significantly improving the impact resistance of the composite material, especially under low temperature conditions, ensuring that the strength and toughness of the material are maintained at a high level to meet the needs of engineering applications.

[0056] (4) The composite material of the present invention has excellent mechanical properties at room temperature and ultra-low temperature, and has a wide applicable temperature range and ultra-low temperature resistance. At room temperature, the impact rod impact test is at least 6 times without breaking, the tensile strength is ≥130MPa, the bending strength is ≥200MPa, the elongation at break is ≥4%, and the simple supported beam notch impact strength is ≥15kJ / m at -50℃. 2 , the impact rod impact test at least once without breaking. It overcomes the low-temperature brittleness problem of traditional nylon glass fiber reinforced composite materials and meets the engineering application requirements in extremely cold environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The process flow chart of some embodiments of the present invention is as follows;

[0058] Figure 2 This is a physical picture of the ultra-low temperature toughened nylon glass fiber reinforced composite material of the present invention. DETAILED DESCRIPTION

[0059] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with the specification and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0060] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0061] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0062] The ultra-low temperature toughened nylon glass fiber reinforced composite material and the preparation method thereof provided by the present invention are further explained below:

[0063] A track shock-absorbing pad, see attached Figure 2 , including ultra-low temperature toughened nylon glass fiber reinforced composite materials, measured by weight, the raw materials of the composite materials include:

[0064] (1) nylon resin, 50-70 parts, including at least one of nylon 6 and nylon 66, nylon 12, nylon 612, nylon 1010 and nylon 1012;

[0065] Preferably, the nylon resin comprises a compound of short carbon chain nylon and long carbon chain nylon, and the mass ratio of the short carbon chain nylon to the long carbon chain nylon is (1-6):(1-3);

[0066] Wherein, the short carbon chain nylon includes at least one of nylon 6 and nylon 66;

[0067] The long carbon chain nylon includes at least one of nylon 12, nylon 612, nylon 1010 and nylon 1012;

[0068] More preferably, the short-chain nylon is pre-mixed with a toughening agent; and the long-chain nylon is pre-cross-linked with a cross-linking agent.

[0069] (2) Glass fiber, 20-40 parts, length 3-6 mm, diameter 10-20 μm, preferably 13-17 μm, and surface treated with a silane coupling agent, the mass ratio of the silane coupling agent to the glass fiber is about 1:(5-50), preferably, the glass fiber is surface treated with a silane coupling agent, specifically comprising the following steps:

[0070] 1) mixing a mercaptosilane coupling agent and glass fiber to form a hydrophobic glass fiber;

[0071] 2) treating the hydrophobic glass fiber with an oxidant to oxidize the thiol groups of the hydrophobic glass fiber to form disulfide bonds, thereby obtaining modified glass fiber.

[0072] The oxidant includes at least one of hydrogen peroxide, organic peroxide, hypochlorite, perborate, permanganate, bromine and nitric oxide. The mercaptosilane coupling agent can be 3-mercaptopropyltrimethoxysilane or 3-mercaptopropylmethyldimethoxysilane.

[0073] (3) Toughener, 5-10 parts, including maleic anhydride modified elastomer, wherein the maleic anhydride modified elastomer includes at least one of maleic anhydride grafted ethylene-octene copolymer and maleic anhydride grafted ethylene propylene diene monomer rubber.

[0074] (4) a cross-linking agent, 0.1-5 parts, comprising an amino cage silsesquioxane, wherein the amino cage silsesquioxane comprises at least one of octaphenylamino cage silsesquioxane, octamethylamino cage silsesquioxane and octaethylamino cage silsesquioxane;

[0075] (5) Other additives, 0.1-10 parts, including: at least one of an antioxidant and a lubricant; the antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant; the lubricant includes at least one of silicone powder and ethylene bis stearamide. Depending on the requirements of the use scenario, masterbatches can also be added to the composite material to obtain products of various colors.

[0076] The method for preparing the ultra-low temperature toughened nylon glass fiber reinforced composite material comprises the following steps:

[0077] S1. Weigh nylon resin, glass fiber, toughening agent, cross-linking agent and other additives according to weight proportions;

[0078] S2, mixing nylon resin, toughening agent, cross-linking agent and other additives;

[0079] S3, adding glass fiber to the mixture, and melt-extruding and granulating to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material.

[0080] More preferably, the raw materials are grouped and pre-mixed, pre-reacted or pre-modified before mixing, so that the synergy between the materials in each group is more sufficient to enhance the overall efficiency of the composite material.

[0081] See attached Figure 1 The method for preparing the ultra-low temperature toughened nylon glass fiber reinforced composite material preferably comprises the following steps:

[0082] S1. Weigh the raw materials according to the weight ratio, and prepare the first raw material group, the second raw material group, and the third raw material group, wherein:

[0083] The first raw material group includes short-chain nylon resin, toughening agent and other additives;

[0084] The second raw material group includes a long-chain nylon resin and a cross-linking agent;

[0085] The third raw material group includes glass fibers surface-treated with a silane coupling agent;

[0086] S2, adding the first raw material group from the main feeding port of the extruder for premixing;

[0087] After the second raw material group is subjected to a pre-crosslinking treatment, it is added from the first side feeding port of the extruder;

[0088] S3, adding the third raw material group from the second side feeding port, setting the working temperature to 200-290°C, the screw speed to 240-600r / min, melt extruding and granulating to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material.

[0089] Example 1

[0090] The ultra-low temperature toughened nylon glass fiber reinforced composite material of this embodiment, measured by weight, comprises the following raw materials:

[0091] (1) Nylon resin, 58.5 parts, including 46.8 parts of nylon 66 (short carbon chain nylon resin) and 11.7 parts of nylon 12 (long carbon chain nylon resin), the mass ratio of the two being 4:1;

[0092] (2) 30 parts of glass fiber surface treated with silane coupling agent, 4 mm in length and 15 μm in diameter, wherein the silane coupling agent is KH550, and the mass ratio of the silane coupling agent to the glass fiber is 1:15;

[0093] (3) toughening agent, 10 parts, selected from maleic anhydride grafted ethylene-octene copolymer (POE-g-MAH);

[0094] (4) cross-linking agent, 1 part, octaphenylamino cage silsesquioxane;

[0095] (5) Other additives, including 0.3 parts of hindered phenol antioxidant and 0.2 parts of silicone powder.

[0096] The method for preparing the composite material specifically comprises the following steps:

[0097] S1, weighing a short carbon chain nylon resin and a long carbon chain nylon resin, maleic anhydride grafted ethylene-octene copolymer, octaphenylamino cage silsesquioxane, a hindered phenol antioxidant, and silicone powder, adding them into a high-speed mixer, and mixing them evenly to obtain a premix;

[0098] S2, adding the premix into the twin-screw extruder from the main feeding port;

[0099] S3, adding glass fiber from a side feeding port, mixing, and melt-extruding and granulating to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material;

[0100] Among them, the temperature of the twin-screw extruder C1 feeding zone is 70°C, the temperature of the C2 heating zone is 275°C, the temperature of the C3 melting zone and the C4 homogenizing zone is 285°C, the temperature of the C5 mixing and plasticizing zone is 290°C, the temperature of the C6 volatile removal zone is 270°C, the temperature of the C7 final melting adjustment zone is 270°C, the temperature of the C8 cooling zone is 270°C, the temperature of the C9 die head temperature control zone is 270°C, and the head temperature is 275°C.

[0101] Example 2

[0102] The difference between Example 2 and Example 1 is that the preparation method is different, and the raw materials are further grouped and refined, including the following steps:

[0103] S1. Weigh the raw materials according to their weight to prepare the first raw material group, the second raw material group and the third raw material group:

[0104] The first raw material group includes 46.8 parts of nylon 66 (short carbon chain nylon resin), 10 parts of maleic anhydride grafted ethylene-octene copolymer, 0.3 parts of hindered phenol antioxidant, and 0.2 parts of silicone powder;

[0105] The second raw material group includes 11.7 parts of nylon 12 (long carbon chain nylon resin) and 1 part of octaphenylamino cage-type silsesquioxane;

[0106] The third raw material group includes 30 parts of glass fiber surface treated with silane coupling agent, with a length of 4 mm and a diameter of 15 μm. The silane coupling agent is KH550, and the mass ratio of the silane coupling agent to the glass fiber is 1:15;

[0107] S2, adding the first raw material group from the main feeding port of the extruder for premixing;

[0108] After pre-crosslinking, nylon 12 and octaphenylamino cage-type silsesquioxane from the second raw material group are added from the first side feed port of the extruder;

[0109] S3, adding the glass fiber of the third raw material group from the second side feeding port of the extruder, melt-extruding and granulating, to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material.

[0110] Embodiment 3-5

[0111] The preparation methods of Examples 3-5 are the same as those of Example 2, but the material composition is adjusted.

[0112] Example 6

[0113] The difference between Example 6 and Example 2 is that the treatment method of the glass fiber is different. The glass fiber in Example 6 is surface treated with a silane coupling agent, which specifically includes the following steps:

[0114] (1) mixing a 3-mercaptopropyltrimethoxysilane coupling agent and glass fiber to form a hydrophobic glass fiber, wherein the mass ratio of the 3-mercaptopropyltrimethoxysilane coupling agent to the glass fiber is 1:15, comprising:

[0115] Dissolve 3-mercaptopropyltrimethoxysilane coupling agent in isopropanol, and add acetic acid to complete the hydrolysis of the silane coupling agent;

[0116] The hydrolyzed silane coupling agent and the glass fiber were stirred and mixed for 15 minutes, the pH value was adjusted to about 7.6 with a sodium hydroxide solution, and heated at about 70° C. for 2 hours to obtain a hydrophobic glass fiber;

[0117] (2) treating the hydrophobic glass fiber with an excess of hydrogen peroxide and continuing to heat at about 70° C. for 1 hour to oxidize the thiol groups of the hydrophobic glass fiber to form disulfide bonds, thereby obtaining modified glass fiber.

[0118] Comparative Example 1-2

[0119] The difference between Comparative Example 1-2 and Example 1 is that Comparative Example 1 uses only short carbon chain nylon 66, and Comparative Example 2 uses only long carbon chain nylon 12.

[0120] The main material compositions of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1:

[0121] Table 1

[0122]

[0123] Test methods and results

[0124] The tensile strength, flexural strength and impact strength under different temperature conditions of the composite materials prepared in Examples 1-6 and Comparative Examples 1-2 were tested respectively, and the results are shown in Table 2 below.

[0125] 1. Impact test method of impact rod at room temperature: The composite materials of Examples 1-6 and Comparative Examples 1-2 were injection molded to obtain samples. Each injection molded sample was fixed on the bottom plate of the impact instrument at 23°C ± 3°C. An impact rod weighing 4.5kg ± 0.05kg was allowed to fall freely from a height of 0.45m, with the impact point being in the middle of the sample.

[0126] 2. Impact bar low temperature impact test method: Place each injection molded sample in a low temperature box at -50℃±3℃ for 30 minutes, quickly take it out of the low temperature box, and perform the impact bar test according to the normal temperature impact test method. The whole process should be completed within 1 minute.

[0127] 3.Tensile strength and elongation at break: tested according to GB / 1040.1-2018.

[0128] 4. Bending strength: tested according to GB / T9341-2008.

[0129] 5. Simple supported beam notched impact strength: tested according to the test standard ISO 179-1:2010.

[0130] The test results of Examples 1-6 and Comparative Examples 1-2 are shown in Table 2:

[0131] Table 2:

[0132]

[0133]

[0134] From the test results, it can be seen that compared with the case of using only a single nylon resin in the comparative example, Examples 1-6 have better comprehensive properties, room temperature simple supported beam notched impact strength ≥30kJ / m2, flexural strength ≥200MPa, tensile strength ≥130MPa, elongation at break ≥4%, preferably ≥5%, the impact rod impact test is at least 6 times without cracking, and the simple supported beam notched impact strength at -50°C is ≥15kJ / m 2 , -50℃ impact test at least once without breaking. In addition, the comprehensive performance of Examples 2-6, which are pre-treated in groups and then blended and melt-extruded, is better than that of Example 1, which is simply blended and melt-extruded, and Example 6, which is modified by treating the glass fiber with 3-mercaptopropyltrimethoxysilane coupling agent and oxidant, has better room temperature and low temperature performance than other examples.

[0135] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention is intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention.

Claims

1. An ultra-low temperature toughened nylon glass fiber reinforced composite material, characterized in that: Servings by weight include: The toughening agent includes a maleic anhydride modified elastomer; The crosslinking agent includes amino cage silsesquioxane; The composite material has a simple supported beam notch impact strength of ≥15 kJ / m at -50°C 2 The impact rod shall not break after at least one impact test at -50℃.

2. The composite material according to claim 1, characterized in that The other additives include at least one of an antioxidant and a lubricant; The antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant; The lubricant includes at least one of silicone powder and ethylene bisstearamide.

3. The composite material according to claim 1, characterized in that The glass fiber has a length of 3-6 mm and a diameter of 10-20 μm, and the surface of the glass fiber is treated with a silane coupling agent.

4. The composite material according to any one of claims 1 to 3, characterized in that The nylon resin comprises a compound of short carbon chain nylon and long carbon chain nylon; The short carbon chain nylon includes at least one of nylon 6 and nylon 66; The long carbon chain nylon includes at least one of nylon 12, nylon 612, nylon 1010 and nylon 1012.

5. The composite material according to claim 4, characterized in that The short carbon chain nylon and the toughening agent are premixed; The long carbon chain nylon is pre-crosslinked with at least a portion of the crosslinking agent; The mass ratio of short carbon chain nylon to long carbon chain nylon is (1-6):(1-3).

6. The composite material according to claim 5, characterized in that The aminated cage silsesquioxane includes at least one of octaphenylamino cage silsesquioxane, octamethylamino cage silsesquioxane and octaethylamino cage silsesquioxane; The maleic anhydride modified elastomer includes at least one of maleic anhydride grafted ethylene-octene copolymer and maleic anhydride grafted ethylene propylene diene monomer rubber.

7. The method for preparing the ultra-low temperature toughened nylon glass fiber reinforced composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh nylon resin, glass fiber, toughening agent, cross-linking agent and other additives according to weight proportions; S2, mixing nylon resin, toughening agent, cross-linking agent and other additives; S3, adding glass fiber to the mixture, and melt-extruding and granulating to obtain the ultra-low temperature toughened nylon glass fiber reinforced composite material.

8. The method for preparing the ultra-low temperature toughened nylon glass fiber reinforced composite material according to claim 7, characterized in that: The nylon resin includes short carbon chain nylon resin and long carbon chain nylon resin, and the glass fiber is surface treated with a silane coupling agent; In step S1, the raw materials are configured into a first raw material group, a second raw material group, and a third raw material group, wherein: The first raw material group includes short carbon chain nylon resin, toughening agent and other additives; The second raw material group includes a long carbon chain nylon resin and a cross-linking agent; The third raw material group includes glass fibers; In step S2, the first raw material group is added from the main feed port of the extruder; After the second raw material group is subjected to a pre-crosslinking treatment, it is added from the first side feeding port of the extruder; In step S3, the third raw material group is added from the second side feeding port.

9. A rail shock-absorbing pad, comprising the ultra-low temperature toughened nylon glass fiber reinforced composite material according to any one of claims 1 to 6 or the ultra-low temperature toughened nylon glass fiber reinforced composite material obtained by the preparation method of the ultra-low temperature toughened nylon glass fiber reinforced composite material according to claim 7 or 8.

10. An application of the ultra-low temperature toughened nylon glass fiber reinforced composite material according to any one of claims 1 to 6 or the ultra-low temperature toughened nylon glass fiber reinforced composite material obtained by the preparation method of the ultra-low temperature toughened nylon glass fiber reinforced composite material according to claim 7 or 8 in rail fastener systems, cable protection sleeves, car interior components, and rail shock-absorbing pads.

Citation Information

Patent Citations

  • A reinforced and toughened ultra-low temperature resistant nylon composite material, its preparation method and application

    CN110437611B

  • A toughened long carbon chain nylon and its preparation method and application

    CN115746557B

Cited By

  • Wear-resistant nylon bar and preparation method thereof

    CN120399443A

  • Impact-resistant chlorinated polyvinyl chloride composite material and preparation method thereof

    CN120775326A